(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Titanium Gr 2 is widely used in engineering and medicine due to its excellent mechanical and corrosion-resistant properties. Laser marking is a crucial process for many applications that require high-contrast, durable markings. In this study, we used a Rofin PowerLine F 20 Varia fiber laser to mark titanium Gr 2 with a 6x6 matrix of 5x5 mm squares. We varied the speed (100-1100 mm/s), power (8-18 W), and frequency (100 and 500 kHz) of the laser marking process to investigate their effects on the surface roughness and contrast of the markings. We analyzed the markings using a laser scanning microscope and Adobe Photoshop software. Our results show that the contrast and roughness of the markings were influenced by the frequency, scanning speed, and power. High marking speeds produced lighter markings, while low marking speeds produced darker markings. We also found that the surface roughness increased with higher frequency and powers. Our findings provide valuable insights into the optimal laser marking parameters for titanium Gr 2, which can enhance its performance and durability in various applications.